MEDIA KOMIK TERHADAP HASIL BELAJAR SISWA - Amirulmukminin, Amirulmukminin; Syahrir, Syahrir (Lensa : Jurnal Kependidikan Fisika, 2014)
The purpose of this study is to determine the effect of comic media on student learning outcomes of class VII MTs School Year 2012/2013. The type of research used is experimental research. The random sampling technique is performed to determine the experimental and control classes. Therefore, VII-A as the experimental class and VII-B is the control class. The experimental class uses comic media as a teaching material for students. Comic media means to design triangle material in comic form. The results showed that U-test (118.5) > U-table (112). We conclude that there is no effect of the use of comic media on students' mathematics learning outcomes.